Leasing a medical curriculum: What's it worth?. (3rd June 2019) - Prideaux, David; Ash, Julie; Broadley, Simon; Crotty, Brendan; Hart, William; Searle, Judy; Watson, Jon; Wing, Lindon; Worley, Paul
Abstract: Introduction: The early part of this century saw an unprecedented growth in number and size of Australian medical schools. There was some partnering of the new schools with existing programs. Griffith, Deakin and Curtin Universities leased an established curriculum from Flinders University. Nature and rationale for curriculum leasing: The new schools had short startup times and leasing a curriculum enabled them to appoint key staff, develop facilities and meet accreditation requirements in a timely way. However, the lease arrangements were costly and the curriculum was largely determined before the Dean and key staff appointments. Outcomes of leasing: There was differential adoption of the leased curriculum. The first two years of the courses at Flinders were transferred with little change. The final two years of predominantly clinical studies were developed differently. This is explained through Michael Fullan's work on context in educational change. The context of the clinical years of the courses involved negotiations with local health services and other schools using those health services. The advantage of the leasing arrangements was that the new schools could proceed through early development and accreditation, while having time and opportunity to negotiate a clinical curriculum that engaged local health services and fulfilled the new schools' missions.